Women’s health issues and safe abortion service for unwanted pregnancies - Rana, Ashma (Nepal Journal of Obstetrics and Gynaecology, 2010)
DOI: 10.3126/njog.v4i1.3323 Nepal Journal of Obstetrics and Gynaecology June-July 2009; 4(1): 1-2